1992
DOI: 10.1002/bjs.1800790626
|View full text |Cite
|
Sign up to set email alerts
|

Body water compartments in patients with obstructive jaundice

Abstract: To elucidate the pathogenesis of renal dysfunction associated with obstructive jaundice, body water compartments were measured using a multi-isotope dilution technique in ten patients with biliary tract obstruction and in ten control subjects matched for age, sex, weight, height and body surface area. Expressed as a fraction of body-weight, total body water was reduced in jaundiced patients (41.8 versus 46.2 per cent, P less than 0.02). Extracellular water volume was also reduced in patients with jaundice (20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 24 publications
3
15
1
2
Order By: Relevance
“…Previous studies have proposed that patients with obstructive jaundice present with hemodynamic and body fluid disturbances [23][24][25]. Our group also demonstrated that extracellular water volume was reduced in the presence of obstructive jaundice [6,7]. Both studies were performed using the same multiisotope dilution technique.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Previous studies have proposed that patients with obstructive jaundice present with hemodynamic and body fluid disturbances [23][24][25]. Our group also demonstrated that extracellular water volume was reduced in the presence of obstructive jaundice [6,7]. Both studies were performed using the same multiisotope dilution technique.…”
Section: Discussionmentioning
confidence: 79%
“…In fact, reactance values are inversely related to extracellular water status [9,15], which seems to be altered in these patients. Previous studies [7] showed that TBW decreased significantly in patients with biliary tract obstruction. In the present study, TBW was also lower in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nedostaci studija na ljudima koje povezuju opstruktivni ikterus i renalnu disfunkciju su razlike u stepenu bilijarne opstrukcije, prisustvo ikterusa ili prisustvo udruženih bolesti (srčana insuficijencija, hronične bolesti jetre, terapija diureticima ili nesteroidnim antinflamatornim lekovima) ili tretmana koji mogu da utiču na renalnu funkciju, a koje je veoma teško ustanoviti [17,18].…”
Section: Diskusijaunclassified